Islamization of the curriculum - Hashim, Rosnani (The Association of Muslim Social Scientists & The International Institute of Islamic Thought, 1999)
This paper makes two important arguments. It demonstrates how the curriculum design is important for the moral and social well-being of individuals as well as societies. Having asserted that, the paper argues that curriculum design depends fundamentally on the well-defined philosophy of education. Without a philosophy of education that can give moral purpose to both individuals as well as societies, it will be difficult to identify a core element that can anchor the curriculum design. The paper then, proceeds to identify the fundamental elements of an Islamic education philosophy and from it elicits the core concerns of an Islamic education curriculum. The paper also discusses several strategies to integrate revealed knowledge and acquired sciences for Muslim universities and schools.